PRIMITIVE IDEALS OF TOEPLITZ ALGEBRA OF ORDERED GROUPS - Rosjanuardi, Rizky (Journal of the Indonesian Mathematical Society, 2008)
The topology on primitive ideal space of Toeplitz algebras of totally ordered abelian groups can be identified through the upwards-looking topology if and only if the chain of order ideals is well-ordered. We describe the topology on primitive ideal space of Toeplitz algebra of totally ordered abelian groups when the chain of order ideals is not well ordered.DOI :Â http://dx.doi.org/10.22342/jims.14.2.55.111-119